Tahap Perkembangan Moral Anak Perspektif Psikologi Pendidikan Islam - Maulida Rahman, Arifani; Ru'iya, Sutipyo; Fauzan Abid , Dzaky (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2022)
This study aims to important role in moral, psychology for Islamic education The results of this study indicate that moral have an important role in a person’s personal behavior. Therefore psychology is a branch of science that is most appropriate in its study because psychology is a branch that studies human behavior (spirit) in particular and in islamic education that psychology has an important role as an instillation of religius awareness related to personal inner values. Recently, Indonesia has just been named the country with the lowest level of politeness on social media in Southeast Asia. Of course, there are many factors that influence this. Moral education has been applied for a long time in Indonesia, of course, the norms of decency enter into it. Could there be a decline in the morale of our nation? In order to prevent this moral decline, there needs to be an evaluation, especially in the field of education. Moral education has been implemented for a long time, but the moral education that is applied needs to be adjusted so that it can improve the moral quality of people in Indonesia